Financing obstacles among euro area firms: Who suffers the most? - Annalisa Ferrando; Nicolas Griesshaber (European Central Bank (ECB), 2011)
In this study we investigate the determinants of financing obstacles using survey data on a sample of around 5000 firms from the euro area countries. This completely new survey – started at the end of 2009 - gives us the opportunity to test whether firm characteristics such as size, age, economic branch, financial autonomy and ownership are valid predictors of financing obstacles also during the recent financial crisis. Our results show that only age and ownership are robust explanatory variables for firms' perceived financing obstacles while mixed results are found for size and economic branches.
Keywords: E22; G30; G10; O16; K40; 330; financial crisis; Financing Constraints; Small and Medium-Sized Enterprises; survey data